Challenges and opportunities to understand, discuss, and decrease maternal mortality rates in the United States. The New Jersey experience. (2nd November 2021) - Apuzzio, Joseph; Gittens-Williams, Lisa; Campbell, Damali; D'Oria, Robyn
Abstract: Maternal mortality improvement depends on the proper classification used in defining maternal deaths. Since there are several definitions of maternal deaths depending upon the proximate cause of the death, if the death is related to the physiologic changes during pregnancy or not and the timing of the death, some opportunities for improvement may be missed to decrease the overall maternal mortality rate in the USA if the correct definition is not utilized appropriately.